Preliminary phytochemical screening, GC-MS profiling and in vitro evaluation of biological activities of garcinia atroviridis root extracts - Nur Salsabila, Ahmad Roslan; Zareen, Seema; Normaiza, Z.; Akhtar, Muhammad Nadeem (IJAR, 2018)
Therapeutic properties of the medicinal plant are due to the presence of phytochemical constituents. Garciniaatroviridis is locally known as ?asamgelugur? belongs to the Guttiferae family. Bioassay-guided solvent-solvent extraction method and yielded, hexane, dichloromethane, ethyl acetate, butanol, and methanolic extracts. These extracts were used to investigate the presence of phytochemicals. The preliminary phytochemical screening showed the existence of fixed oils and fats, carbohydrate, saponins, phenolic, flavonoids and anthraquinone glycosides in G. atroviridis roots. The chemical compositions were investigated by using Gas Chromatography-Mass Spectroscopy (GC-MS). Major compound identified in hexane, DCM, EA, BuOH and methanolic extracts was (Z)-13-docosenoic acid methyl ester (24.32%), ethyl-9-hexadecenoate (6.36%),bis(1,3-diisopropylcyclopentadienyl) (12.09%), 2-methyl-2-phenyl- 1,3-dioxolane (2.34%) and furfural (33.55%) respectively. The antibacterial and antioxidant activities of the extracts were investigated. The methanolic crude extract exhibited resistance towards both bacteria tested; Bacillus subtilisand Escherichia coli, thus suggesting its antibacterial activity.